Kondaṇẽ : nāṭya, saṅgīta, sāhitya, ityādi vishayã̄varīla ṭikātmaka va varṇanātmaka lekhāñcā saṅgraha - Phadke, Narayan Sitaram (SAMP early 20th-century Indian books project, 1947)
Articles on Marathi literature.